(untitled) (Salduie, 2024)
This site is integral to the World Heritage designation ’Rock Art of the Mediterranean Basin on the Iberian Peninsula’. This research unveils findings from a non-invasive, in situ multi-elemental composition analysis of pigments employed in eight key shelters. The analysis, conducted through portable X-ray fluorescence spectroscopy (pXRF), focuses on the cave paintings of Chimiachas, Muriecho, and Arpán (representing Levantine Art), as well as Mallata, Barfaluy, Quizans, Lecina Superior, and Forau del Cocho (representing Schematic Art). Across all River Vero rock shelters, red pigments dominated, composed of iron minerals, with Fe concentrations ranging from 0.51% to 3.06%. Mallata B1 and I, Muriecho, and Forau del Cocho exhibited higher iron content compared to Arpán, Barfaluy, Lecina, and Chimiachas, which, in turn, surpassed Quizans. These variations suggest significant differences in conservation status. Black pigments, devoid of manganese, were linked to bone char or vegetal carbon black. The presence of phosphorus indicates the utilization of bone phosphates in the paints, either as a filler or as a binder. Geological assessments reveal that the identified gypsum originates externally, likely associated with gypsum-rich atmospheric dust.